Parthenolide improves sepsis-induced coagulopathy by inhibiting mitochondrial-mediated apoptosis in vascular endothelial cells through BRD4/BCL-xL pathway - Jun Zhang; Xing Zhu; Yong Li; Yinyu Wu; Yunxia Du; Hai Yang; Zhengchao Liu; Haoyu Pei; Rui Li; Huan Luo; Deyu Zuo; Han She; et al. (Journal of Translational Medicine)
Abstract Background Sepsis is a systemic inflammatory syndrome that can cause coagulation abnormalities, leading to damage in multiple organs. Vascular endothelial cells (VECs) are crucial in the development of sepsis-induced coagulopathy (SIC). The role of Parthenolide (PTL) in regulating SIC by protecting VECs remains unclear. Methods The study utilized septic rats and lipopolysaccharide (LPS)-stimulated VECs to simulate a SIC model and observe the therapeutic effects of PTL. Additionally, nanotechnology was employed to produce Nano-PTL (N-PTL), to observe whether it has advantages over PTL in treating SIC. Results PTL has been shown to mitigate lung injury in septic rats, significantly reduce tumor necrosis factor-α (TNF-α) levels, and increase survival rates. PTL treatment also enhances coagulation function, augments vascular endothelial cell (VEC) function, reduces mitochondrial fragmentation, and increases both mitochondrial oxygen consumption rate (OCR) and mitochondrial membrane potential (MMP), while inhibiting reactive oxygen species (ROS) production. By increasing BRD4/BCL-xL levels, PTL can prevent mitochondrial-mediated apoptosis in VECs, improve VEC function, and consequently ameliorate SIC. Additionally, nanotechnology-synthesized N-PTL further enhances the protective effects on VECs and coagulation function. Conclusions This study clarifies the therapeutic effects and mechanisms of PTL on SIC, offering new strategies and directions for the treatment of sepsis.